Risk Assessment of Safety Management System Implementation on the Training Ship Barombong Using the House of Risk Method - Rina Haryani; Sidrotul Muntaha; Yudi Satria; Rachmat Tjahjanto (Politeknik Siber Cerdika Internasional, 2026)
Background: The shipping industry has a high level of operational risk, making the implementation of a safety management system a crucial aspect to ensure the safety of the crew, passengers, and ship operations. The Barombong Shipping Polytechnic Training Ship, as a means of education and pioneer transportation, also faces various potential risks that can affect the effectiveness of the implementation of the Safety Management System (SMS). Objective: This study aims to analyze the influence of risk assessment using the House of Risk method on the implementation of the SMS on the Barombong Training Ship and to identify the dominant risk factors affecting operational safety. Method: This research used a descriptive analytical approach with the House of Risk method through the stages of identifying risk events and risk agents, assessing risk probability and impact, and calculating the Risk Priority Number (RPN) to determine mitigation priorities. Data were obtained through field observations, interviews with ship crew, documentation studies, and analysis of Safety Management System reports. Result: The research results indicate that several main risks in SMS implementation include non-conformity with safety procedures, lack of training and emergency drills, and suboptimal safety documentation. Risks with the highest RPN values become the top priority in the mitigation strategy. Conclusion: The application of the House of Risk method is proven to help identify, prioritize, and design risk control strategies more systematically, thereby enhancing the effectiveness of Safety Management System implementation and supporting a safety culture on the Barombong Training Ship.